One mole digging a hole - Julia Donaldson
All the animals are busy lending a hand in the garden in this lively numbers book! The parrots are pulling up carrots, the foxes are filling boxes and a swarm of bees are pruning the trees with their miniature shears. Even the smallest toddler will enjoy the wonderfully silly animal antics in this book, so join in and count along -- gardening has never been so much fun! Trademark Julia Donaldson rhymes and rhythms are perfect to read aloud, and Nick Sharratt's mischievous and funny illustrations make this bright and playful book a sure winner. Just right for toddlers!
Early Years